A new record of Nymphaea (Nymphaeaceae) for Flora of Nepal - Raskoti, Bhakta B; Ale, Rita; Bhatt, Ganga D (Botanica Orientalis: Journal of Plant Science, 2012)
Occurrence of Nymphaea lotus var. pubescens Willd. (Nymphaeaceae) in Nepal is reported. Detailed description, illustration and relevant notes are provided. doi: http://dx.doi.org/10.3126/botor.v8i0.5958 Botanica Orientalis – Journal of Plant Science (2011) 8: 105-107